RETRACTED: An empirical investigation of the impact of renewable and non-renewable energy consumption and economic growth on climate change, evidence from emerging Asian countries - Zhao, Jingyun; Zhang, Taiming; Ali, Arshad; Chen, Jian; Ji, Houqi; Wang, Tiantian (Frontiers in Environmental Science, 2023)
One of the greatest challenges facing humanity in the current millennium is the need to mitigate climate change, and one of the most viable options to overcome this challenge is to invest in renewable energy. The study dynamically examines the impact of renewable and non-renewable energy consumption and economic growth on climate change, using Augmented Mean Group (AMG) technique in emerging Asian countries during the period 1975-2020. The estimated results show that the consumption of renewable energy sources significantly mitigates climate change, while the consumption of non-renewable energy sources significantly contributes to climate change. Furthermore, economic growth, investment in transport infrastructure, and urbanization significantly accelerate climate change in specific emerging Asian countries. The results further demonstrate the validity of the inverted U-shaped EKC hypothesis in emerging Asian economies. Country-specific analysis results using AMG estimates shows that renewable energy consumption reduces climate change for all specific emerging Asian countries. However, the consumption of non-renewable energy sources and investments in transport infrastructure have significant incremental impacts on climate change in all countries. Urbanization contributes significantly to climate change, with the exception of Japan, which does not have any significant impact on climate change. The significant progressive effect of GDP and the significant adverse impact of GDP2 on climate change confirm the validity of the inverted U-shaped EKC hypothesis in India, China, Japan, and South Korea. Moreover, the Dumitrescu and Hurlin causality test confirmed a pairwise causal relationship between non-renewable energy consumption and GDP, supporting the feedback hypothesis. According to the empirical analysis of this study, the best strategy for climate change mitigation in specific emerging countries in Asia is to transition from non-renewable energy to renewable energy.